Життєпис Лесі Українки в родинному листуванні Олени Пчілки - Оніпко, Вячеслав; Onipko, Vіacheslav (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті йдеться про значення епістолярної спадщини Олени Пчілки в сучасному джерелознавстві. Зроблено аналіз праць, пов’язаних із цією про- блемою. На прикладі життєпису Лесі Українки показано роль листів Олени Пчілки як джерела вивчення біографії. На основі епістолярної спадщини матері висвітлено епізоди з життя Лесі Українки, родинні стосунки. In the article it’s said about the importance of epistolary heritage Olena Pchilka in the modern source. It is noted that the study of the autographs of the letters helps to explore the biography not only Pchilka, but members of her family, acquaintances, to study the events in the culture and art of movement at the end of IX beginning of XX century. A study is made analyze of work related to this problem. For example, the biography of Lesіa Ukrainka’s the role of letters Olena Pchilka as sources for the study of the biographies of their relatives. The article on the basis of Olena Pchilka’s letters highlights various moments in the life of Lesіa Ukrainka, family relationships. Also illustrated with excerpts from Pchilka’s letters the individual facts of publishing of works, illness of Lesіa Ukrainka.
The Lesіa Ukrainka’s Life over Olena Pchilka’s Family Correspondence
Keywords: епістолярій; лист; автограф; джерело; джерелознавство; epistolary; letter; autograph; source; manuscript